PROSEDUR PENDAFTARAN DAN PENGALIHAN MEREK SERTA UPAYA PERLINDUNGAN HUKUM TERHADAP MEREK TERKENAL MENURUT UNDANG-UNDANG NOMOR 15 TAHUN 2001 - Gossain Jotyka; I Gusti Ketut Riski Suputra (Ganesha Law Review, 2021)
Based on Article 1 of Law No.15 of 2001 concerning Marks, what is meant by Mark is signs in the form of pictures, names, words, numeric letters, color arrangements, or a combination thereof these elements which have distinctive power and are used in the world of commerce goods or services. The marks are trademarks and service marks. The collective brand is a brand used on goods or services with the same characteristics that are traded by several people or legal entities together to differentiate goods or services the like. In a trademark there is a license term, namely a license granted by the owner of the registered mark to a person or persons collectively or a legal entity for use the mark, for goods or services. In the world of trade it often happens brand violation. Trademark infringement is basically committed by parties who have bad ethics to make a profit, which can harm the brand owner legitimate. Indications of violations based on Trademark Law No.15 of 2001, exist several classifications regarding brand counterfeiting, namely using the same mark as a whole, using the same brand in essence, using the same mark, uses the same mark substantially as the geographical indication. Apart from that there are also counterfeiting of registered marks. In fact, registered trademarks must be protected by the State through Trademark law